1991
DOI: 10.1126/science.254.5030.399
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Formation of Ontong Java Plateau by Aptian Mantle Plume Volcanism

Abstract: The timing of flood basalt volcanism associated with formation of the Ontong Java Plateau (OJP) is estimated from paleomagnetic and paleontologic data. Much of OJP formed rapidly in less than 3 million years during the early Aptian, at the beginning of the Cretaceous Normal Polarity Superchron. Crustal emplacement rates are inferred to have been several times those of the Deccan Traps. These estimates are consistent with an origin of the OJP by impingement at the base of the oceanic lithosphere by the head of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
166
0
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(169 citation statements)
references
References 35 publications
0
166
0
3
Order By: Relevance
“…Paleomagnetic data from Site 807 show that the basalt and overlying limestone are of normal polarity (Tarduno et al, 1991;Mayer and Tarduno, this volume) Harland et al (1990), we lack the means at present to correlate the paleontologic datums during the Barremian and early Aptian. Accordingly, in this paper we continue to use the correlations of Harland et al (1982) and Kent and Gradstein (1985).…”
Section: Biochronology and Geochronologymentioning
confidence: 99%
See 2 more Smart Citations
“…Paleomagnetic data from Site 807 show that the basalt and overlying limestone are of normal polarity (Tarduno et al, 1991;Mayer and Tarduno, this volume) Harland et al (1990), we lack the means at present to correlate the paleontologic datums during the Barremian and early Aptian. Accordingly, in this paper we continue to use the correlations of Harland et al (1982) and Kent and Gradstein (1985).…”
Section: Biochronology and Geochronologymentioning
confidence: 99%
“…The revised time scale of Harland et al (1990) now places the Hedbergella similis Zone in the latest Barremian and dates the top of ReversedPolarity Chron M0 at 124 Ma and the Barremian/Aptian boundary, still defined by the first appearance of Chiastozygus litterarius, at 124.5 Ma. Little information is given as to the reasons for revising the microfossil biostratigraphy (see discussion in Tarduno et al, 1991). In fact, revision of the Barremian to early Aptian planktonic foraminiferal datums is required based on new data from Leckie and Bralower (1991) and Coccioni et al (1992).…”
Section: Biochronology and Geochronologymentioning
confidence: 99%
See 1 more Smart Citation
“…The Phoenix-Japanese ridge junction is concealed beneath the Ontong Java Plateau of middle Cretaceous age (Tarduno et al, 1991) and the Caroline Rise of Tertiary age, both of which may also represent mantle plumes.…”
Section: Ridge Configuration and Oceanic Plateausmentioning
confidence: 99%
“…It has been suggested that the long Cretaceous normal magnetic polarity epoch may be related to a super plume in the SW Pacific Ocean that gave rise to the Ontong Java plateau (Tarduno et al 1991), and it has recently been established that the deep mantle super plume under Africa is connected to the surface by smaller plumes (Bagley and Nyblade 2013).…”
Section: Thermochemical Plumesmentioning
confidence: 99%